Common Variable Immunodeficiency Associated with Hepatosplenic T-Cell Lymphoma Mimicking Juvenile Systemic Lupus Erythematosus - A. A. Jesus; C. M. A. Jacob; C. A. Silva; M. Dorna; A. C. Pastorino; M. Carneiro-Sampaio (Clinical and Developmental Immunology)
Common variable immunodeficiency (CVID) is a heterogeneous disorder with susceptibility to infections, autoimmune manifestations, and cancer. To our knowledge, CIVD with T-cell lymphoma mimicking juvenile systemic lupus erythematosus (JSLE) was not described in the literature, and one case was reported herein. An 8-year-old female was admitted in our Pediatric Immunology Unit with a clinical history of hypogammaglobulinemia, recurrent upper respiratory infections, and pneumonias. She had a marked decrease of three serum immunoglobulin isotypes, and the diagnosis of CVID was established. At the age of 17 years, she presented with oral ulceration, nonerosive arthritis, nephritis, serositis, cytopenia, positive antiphospholipid antibodies, and positive antinuclear antibody fulfilling the American College of Rheumatology (ACR) criteria for SLE. She was treated with intravenous methylprednisolone for three consecutive days, and intravenous immunoglobulin, and maintenance therapy of chloroquine, azathioprine and prednisone 40 mg/day. Two months later, she died of septic shock secondary to acute pneumonia. The necropsy showed hepatosplenic T-cell lymphoma with diffuse involvement of bone marrow, spleen, liver, and lungs. The lymphoma cells were positive for CD3 immunostaining and negative for CD20 and lysozyme. In conclusion, the association of CVID and hepatosplenic T-cell lymphoma may simulate JSLE diagnosis.